Respuesta :

Answer:

x = 1

Step-by-step explanation:

Solve for x:

-103 x - 6 = -6 x - 103

Add 6 x to both sides:

6 x - 103 x - 6 = (6 x - 6 x) - 103

6 x - 6 x = 0:

6 x - 103 x - 6 = -103

6 x - 103 x = -97 x:

-97 x - 6 = -103

Add 6 to both sides:

(6 - 6) - 97 x = 6 - 103

6 - 6 = 0:

-97 x = 6 - 103

6 - 103 = -97:

-97 x = -97

Divide both sides of -97 x = -97 by -97:

(-97 x)/(-97) = (-97)/(-97)

(-97)/(-97) = 1:

x = (-97)/(-97)

(-97)/(-97) = 1:

Answer:  x = 1

Answer:

x = 1

Step-by-step explanation:

  1. [tex] - 103x - 6 = - 6x - 103[/tex]
  2. [tex] - 103x + 103x - 6 = - 6x + 103x - 103[/tex]
  3. [tex] - 6 = 97x - 103[/tex]
  4. [tex] - 6 + 103 = 97x - 103 + 103[/tex]
  5. [tex]97 = 97x[/tex]
  6. [tex]\frac{97}{97} = \frac{97x}{97} [/tex]
  7. [tex]1 = x[/tex]